Age, Parity, and The Prevalence of Anemia in Third-Trimester Pregnant Women: A Correlation Study - Anggraini Dyah Setiyarini; Ayu Rosita Dewi (Health and Technology Journal (HTechJ), 2025)
Lack of iron the most prevalent type of anemia during pregnancy is and is still a global health problem. Both the mother and the unborn child are impacted by anemia. Data on pregnant women who experience anemia in Desa Semen in 2025 were 8 pregnant women. This study aimed to ascertain how age and parity relate to the prevalence of anemia in the third trimester of pregnancy in Semen Village, Semen Subdistrict, Kediri Regency. The study employed a cross-sectional methodology. There were fifteen participants in the study, which was carried out in Semen Village; Total sampling was used as the sampling method. A questionnaire on the mother's age and parity as well as the findings of laboratory tests to evaluate the anemia status were employed in the data-gathering process. Chi-square was utilized in both univariate and bivariate data analysis. The study revealed that the number of pregnant women at risk (less than 20 years and more than 35 years) was 7 (46.7%), and the number of pregnant women at risk (more than three times) was 7 (46.7%). Seven individuals (46.7%) had normal hemoglobin levels (≥11 g/dl) throughout pregnancy, while eight individuals (53.3%) had abnormal hemoglobin levels (<11 g/dl). The study of parity and age with the incidence of anemia revealed a p-value of 0.032 (p < 0.05) and 0.032 (p < 0.05), respectively. Additionally, in Semen Village, Semen Subdistrict, Kediri Regency, there is a correlation between the incidence of anemia in the third trimester of pregnancy and age, as well as between parity and anemia incidence. Researchers hope to program pregnancy at the ideal age and pay attention to the number of parities so that pregnancy is safer and healthier.